Men Scare Me More: Gender Differences in Social Fear Conditioning in Virtual Reality - Reichenberger, Jonas; Pfaller, Michael; Forster, Diana; Gerczuk, Jennifer; Shiban, Youssef; Mühlberger, Andreas (Frontiers in Psychology, 2019)
Women nearly twice as often develop a social anxiety disorder (SAD) than men. The reason for this difference is still on debate. The present study investigates gender differences and the effect of male versus female agents in low (LSA) and high socially anxious (HSA) participants regarding the acquisition and extinction of social fear in virtual reality (VR). In a social fear conditioning (SFC) paradigm, sixty participants actively approached several agents, some of which were paired with an aversive unconditioned stimulus (US) consisting of a verbal rejection and spitting simulated by an aversive air blast (CS+), or without an US (CS–). Primary outcome variables were defined for each of 4 levels of emotional reactions including experience (fear ratings), psychophysiology (fear-potentiated startle), behavior (avoidance), and cognition (recognition task). Secondary outcome variables were personality traits, contingency ratings, heart rate (HR), and skin conductance response (SCR). As hypothesized, fear ratings for CS+ increased significantly during acquisition and the differentiation between CS+ and CS– vanished during extinction. Additionally, women reported higher fear than men. Furthermore, a clear difference in the fear-potentiated startle response between male CS+ and CS– at the end of acquisition indicates successful SFC to male agents in both groups. Concerning behavior, results exhibited successful SFC in both groups and a general larger distance to agents in HSA than LSA participants. Furthermore, HSA women maintained a larger distance to male compared to female agents. No such differences were found for HSA men. Regarding recognition, participants responded with higher sensitivity for agent than object stimuli, suggesting a higher ability to distinguish the target from the distractor for social cues, which were on focus during SFC. Regarding the secondary physiological outcome variables, we detected activation in HR response during acquisition, but no differences between stimuli or groups. Moreover, we observed a gender but no CS+/CS– differences in SCR. SFC was successfully induced and extinguished according to the primary outcome variables. VR is an interesting tool to measure emotional learning processes on different outcome levels with enhanced ecological validity. Future research should further investigate social fear learning mechanisms for developing more efficient treatments of SAD.